The Sculptures from the Amphitheater of Verona (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The paper gives an updating of the available information about the sculptures from the Roman Amphitheater in Verona and about the internal furniture of the monument, after the finding or a new reading of old documents; then the historical data related to the games in the Veronese Arena are re-examined.
Keywords: Verona; amphitheater; Arena; roman sculpture; gladiatorial games; venationes; munera